Assessing Entrepreneurial Types and Goals With Diverse Student Groups. (30th January 2023) - Bendickson, Josh; Matherne, Curtis F.; Credo, Keith R.; Franques, Mary Catherine O.; Sheats, Lewis
Students should clearly understand that different types of entrepreneurship exist. It is effective to connect the diversity of entrepreneurial form with students from a multidisciplinary scope of knowledge in the form of engaged learning. This learning innovation exercise helps diverse student bodies such as science, technology, engineering, arts, and math students (STEAM), to apply their knowledge of entrepreneurship basics and each entrepreneurship type and to be prepared to verbally defend their decisions in the presence of other future entrepreneurs. Although this exercise follows Steve Blank's categorization of entrepreneurship types (i.e., small business entrepreneurship, scalable startup entrepreneurship, large company entrepreneurship, and social entrepreneurship), educators adopting this exercise can readily replace or add other entrepreneurship types that are more relevant to a specific course or that (s)he wishes for students to more fully understand. This learning innovation is intended for implementation at the undergraduate level in medium sized introduction to entrepreneurship courses that includes students from STEAM. Students will gain experience in analyzing and problem solving related to the different types of entrepreneurship. Students will also be provided the space for group discussion and personal decision making thus fostering the development of crucial entrepreneurial skills necessary after graduation.